Environmental capabilities, environmental innovation, and firm performance of manufacturing companies in Malaysia - Lee, Ah Suat (2018)
Business firms are increasingly adopting proactive environmental management as business strategy to address environmental challenges and enable the shift to green market competition. In doing so, it is crucial for these firms to be equipped with environmental capabilities for sustaining firms’ competitive capabilities in terms of environmental performance and innovation, which would eventually lead to superior firm performance. However, to date businesses are still uncertain about what kind of environmental capabilities could enhance firm performance. This is because extant empirical research had largely focused on examining direct effects of proactive environmental management on firm performance. Thus, this study examined how dynamic capabilities emerged from proactive environmental practices foster the creation of environmental capabilities that in turn enhances firms’ competitiveness and financial performance. Further, the natural resource-based theories have clearly specified innovation as the core factor enabling superior firm performance from environmental management. In view of limited empirical studies in this perspective, this study examined the mediating role of environmental innovation. Data collection was executed using a survey study over a period of one year in 2017. A total of 124 responses were collected from managers of EMS14001 certified manufacturers in Malaysia, and data was subjected to a structural equation analysis using the Smart PLS version 3.2.7 software. Results indicated that environmental strategic focus and environmental collaboration directly enhance environmental performance. While, environmental technological capabilities exert a counteracting effect on environmental performance. In addition, environmental technological capabilities and environmental collaboration were found to directly enhance environmental innovation. On the other hand, environmental strategic focus indirectly enhances environmental innovation via environmental performance. However, contrary to prediction, results failed to validate environmental shared vision and environmental management support as environmental capabilities, as both construct do not directly contribute to both environmental performance and environmental innovation. Results also endorse environmental innovation as the key enabler for the creation of economic values from environmental management. This is owing to its function as the sole factor that directly contributes to firm performance both in terms of competitive advantage and financial performance. Moreover, environmental innovation is also found to be the full mediator that translates benefits of environmental performance into competitive advantage and financial performance. Further, despite the apparent role of environmental performance as environmental value, it does not exert direct influence on competitive advantage nor financial performance. Instead environmental performance has an indirect effect on competitive advantage and financial performance through environmental innovation. This study integrates theories of dynamic capabilities and the natural resource-based theories, and establishes a research model for analysing proactive environmental management. The study validated the predictive role of environmental capabilities and the mediating role of environmental innovation, and revealed the significant paths leading to superior firm performance among environmentally proactive manufacturers in Malaysia. Findings confirmed that achievements in environmental innovation would likely convert manufacturers’ strengths in environmental management into market related benefits, thus resulting in superior financial performance. Overall, findings of this study provide useful insights to manufacturers and the Malaysian Government in crafting environmental policy and strategies.